Factors associated with risk of smartphone addiction among undergraduate university students in Kelantan - Rahim, Nurfarhan (2017)
Background: Excessive smartphone use could lead to addiction. Smartphone addiction has become a recent concern because of its potential to adversely impact on many aspects of life. The aim of this study is to assess the level of risk for smartphone addiction and to identify the predictors on the smartphone addictive behaviour among undergraduate university students in Kelantan. Methods: This is a cross-sectional study conducted among 140 students of School of Health Sciences USM. Students from five study programs were randomly selected through multistage cluster sampling method. Socio-demographic and smartphone usage characteristic proforma, Smartphone Addiction Scale Malay Version (SAS-M) to measure the level of risk for developing smartphone addiction and Depression Anxiety Stress Scale 21 – Malay Version (DASS 21) to measure depression, anxiety and stress level; were selfadministered by the students. Results: The mean score of SAS was 111.07 (SD 25.11). Majority of the students used smartphone for more than four hours daily (78.6 %). Daily usage smartphone time (13.63, 95% CI: 4.18, 23.08, p = 0.005) and stress level (1.57, 95% CI: 0.51, 2.62, p = 0.004 ) were found to have significant positive relationship, while Audiology program (-12.98, 95% CI: -24.43, -1.54, p = 0.027) and family income less than RM1000 (-12.52, 95% CI: -21.54, - 3.50, p = 0.007) have significant negative relationship with SAS-M score.